Asymmetric Organocatalytic Tandem Cyclization/Transfer Hydrogenation: A Synthetic Strategy for Enantioenriched Nitrogen Heterocycles. Issue 18 (27th November 2013) - Shi, Feng; Tan, Wei; Zhang, Hong‐Hao; Li, Mei; Ye, Qin; Ma, Guan‐Hua; Tu, Shu‐Jiang; Li, Guigen
Abstract An asymmetric organocatalytic tandem reaction comprising cyclization/transfer hydrogenation has been established in a compatible and synergistic way, leading to the step‐economical synthesis of enantioenriched tetrahydroquinoxalines and dihydroquinoxalinones from readily accessible materials in excellent enantioselectivity of up to >99% ee. This protocol of a one‐operation tandem reaction combines the merits of both tandem reactions and asymmetric organocatalysis, providing an efficient strategy for concisely and enantioselectively synthesizing nitrogen heterocycles with biological relevance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>